The Expression of National Mentality through Irony in English and Uzbek Literature - AbduqodirovaMadinaAbduqayumqizi (Academia One Publishing, 2025)
This study examines how irony functions as a literary tool to convey national identity in both English and Uzbek literary traditions. Focusing on the writings of William Shakespeare and Hamid Olimjon Uygun, the research highlights how each author reflects the moral and cultural values of their societies through different types of irony. Shakespeare’s works use irony to question power structures and social appearances in the Elizabethan context, while Uygun applies metaphorical and symbolic irony to comment on societal issues under Soviet limitations. The paper also explores the linguistic and cultural challenges involved in translating irony between English and Uzbek, showing how deeply it is rooted in national ways of thinking and expression
Keywords: Irony; national identity; Shakespeare